MILITARY PATRIOTISM AS A SOCIO-PHILOSOPHICAL PHENOMENON IN THE CONTEXT OF GLOBAL SECURITY TRANSFORMATION (2015–2025) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article is devoted to the philosophical analysis of military patriotism as a complex socio-cultural and axiological phenomenon formed in the context of the transformation of global threats and changes in the structure of international security in 2015–2025. The need to revise the traditional models of patriotic education and the formation of a new paradigm of "responsible patriotism" focused on humanistic values and civic maturity is substantiated.